Efficacy of a feed additive consisting of tartrazine for its use in baits for freshwater fish (GIFAP) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the efficacy of tartrazine. Tartrazine is intended to be used as a sensory additive (functional group: (a) colourants: (i) substances that add or restore colour in feedingstuffs) in baits for freshwater fish up to a maximum content of 30 mg/kg in complementary feed. Tartrazine is intended to be incorporated in fishing baits in order to colour them and attract fish in freshwater (ponds, rivers), for both recreational and competitive fishing. The additive is not intended for use in aquaculture. The characterisation of the additive, its safety and its efficacy were evaluated in a previous opinion of the Panel. In that opinion, the Panel concluded that the use of tartrazine in the preparation of baits for freshwater fish under the proposed conditions of use (maximum use level of 30 mg/kg complementary feed) is of no concern for the target animals. The use of tartrazine as a feed additive under the proposed conditions of use is considered safe for the consumer and the environment. Regarding the user safety, the additive should be considered a dermal and respiratory sensitiser. Inhalation and dermal exposure are considered a risk. The FEEDAP Panel could not conclude on the irritation potential of the additive. Finally, in the previous opinion, the Panel concluded that in absence of data no conclusion could be reached on the efficacy of tartrazine in freshwater fish baits. Based on the new data submitted by the applicant, the Panel concluded that tartrazine has the potential to be efficacious in colouring fishing baits under the proposed conditions of use.